Powder metallurgy (Fundamental manufacturing processes, 2000)
Powder metallurgy is a metalworking technology used for producing parts from metal powder. Its primary advantages include part design flexibility and the ability to produce net or near-net shaped parts using various processes. These processes include mechanical pressing of powder, metal injection molding, hot and cold isostatic pressing and metal powder production methods.